KEBIJAKAN PENYALURAN PEKERJA MIGRAN MASA PANDEMI COVID -19 DI KABUPATEN PONOROGO - Nirma Vinny Rahayu; Ekapti Wahjuni DJ; Dian Suluh Kusuma D; Bambang Triono (Fakultas Politik Pemerintahan IPDN, 2022)
Abstract Indonesia has experienced a pandemic over the past three years, which is remarkable and has caused the spread of Pekerja Migran Indonesia (PMI) abroad. The end of PMI distribution during the outbreak of the Covid-19 pandemic in Indonesia led to various policies in the Labor offices (Disnaker) and PMI distribution in PT. Tulus Widodo Putra and PT Andhika Putra Mandiri during the pandemic. The purpose of this study is to determine the policies of the Ministry of Manpower and analyze the distribution of Indonesian labor in PT. Tulus Widodo Putra and PT. Andhika Independent Son. The research method uses an explanatory description with a qualitative approach. The informant determination technique uses purposive sampling techniques. Research shows that the policy was made to stop the distribution of Migrant Workers abroad, which significantly impacts PT. Tulus Widodo Putra and PT. Andhika Putra Mandiri and all prospective Migrant Workers in the two universities. The research results in the field showed that during the Covid-19 pandemic, the operation was dismissed, and all shelters were vacated to prevent the accidental transmission of the Covid-19 virus. Still, one of these companies did not follow the instructions of the Ponorogo Regency Manpower Office. Keywords: Covid – 19 pandemic, Policy, PMI Distribution